2012
DOI: 10.1007/bf03262194
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effects of Salidroside on Epirubicin-Induced Early Left Ventricular Regional Systolic Dysfunction in Patients with Breast Cancer

Abstract: Background: Salidroside [2-(4-hydroxyphenyl)ethyl-b-D-glucopyranoside], one of the most potent ingredients extracted from the plant Rhodiola rosea L., has been shown to have a cardiovascular protective effect as an antioxidant, and early treatment of epirubicin-induced cardiotoxicity has been the focus of clinical chemotherapy in patients with breast cancer. However, the cardioprotective effects of salidroside on epirubicin-induced cardiotoxicity, especially early left ventricular regional systolic dysfunction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 19 publications
(18 reference statements)
0
19
0
2
Order By: Relevance
“…Salidroside (p-hydroxyphenethyl-β-D-glucoside) is a major phenylpropanoid glycoside present in Rhodiola species. Various pharmacological properties, including antiaging, neuroprotective, anti-inflammatory, hepatoprotective, and antioxidant effects have all been reported for this compound [34][35][36][37][38]. In addition, studies have demonstrated the antitumoral effects of salidroside through its inhibition of cell proliferation, arrest of the cell cycle, and induction of apoptosis in human bladder, breast, lung, and liver cancer cells [39,40].…”
Section: Pharmacological Data Concerning the Pure Compound Salidrosidementioning
confidence: 96%
“…Salidroside (p-hydroxyphenethyl-β-D-glucoside) is a major phenylpropanoid glycoside present in Rhodiola species. Various pharmacological properties, including antiaging, neuroprotective, anti-inflammatory, hepatoprotective, and antioxidant effects have all been reported for this compound [34][35][36][37][38]. In addition, studies have demonstrated the antitumoral effects of salidroside through its inhibition of cell proliferation, arrest of the cell cycle, and induction of apoptosis in human bladder, breast, lung, and liver cancer cells [39,40].…”
Section: Pharmacological Data Concerning the Pure Compound Salidrosidementioning
confidence: 96%
“…Die Studie zeigte eine signifikante Normalisierung der Herzfunktion in der Salidrosidgruppe. Die Autoren der Studie verweisen damit auf eine deutliche kardioprotektive Wirkung von Salidrosid und schlagen die Verwendung dieser Verbindung zur Verhinderung unerwünschter Wirkungen bei Epirubicin-Therapie vor [24].…”
Section: Kardioprotektive Wirkungunclassified
“…Zur Embryotoxizität von Salidrosid gibt es noch keine verlässlichen Daten. Eine Behandlung mit 600 mg Salidrosid pro kg Körpergewicht pro Tag bei 60 Krebspatienten wurde gut toleriert [22], [24]. Bei Dosierungen von 200-600 mg Extrakt treten selten unerwünschte Wirkungen wie Angst, Agitation und Zittern auf.…”
Section: Toxikologieunclassified
“…Therefore, they have potential uses in cardiovascular diseases, cancer, and AIDS [17]. Salidroside confers protection from brain cell damage [18] and bone loss [19] and reduces the side effects of chemotherapy [20].…”
Section: Classification and Biological Activities Of Phenylethanoidsmentioning
confidence: 99%